Advances in sustainable grinding of different types of the titanium biomaterials for medical applications: A review - Ronoh, Kipkurui; Mwema, Fredrick; Dabees, Sameh; Sobola, Dinara (Biomedical engineering advances, 2022)
This review discusses various grades of titanium biomaterials and their sustainable grindability for application in the medical field. Titanium biomaterials are most commonly utilized for medical applications due to their exceptional characteristics such as high corrosion resistance and biocompatibility. The presented review looks at the principal requirements of titanium for medical applications, such as some good mechanical properties, biocompatibility, corrosion, wear resistance properties, and processability that facilitate the successful implantation of implants. It discusses the various types of titanium alloys that are commercially available and, more specifically, used for medical applications. It highlights the properties of different grades of titanium alloys and further narrows down its primary focus on applications, advantages, and shortcomings of commercially available titanium biomaterials. Machining titanium alloys is a difficult task due to their inherent properties such as low thermal conductivity and chemical reactivity at high temperatures and usually results in changes in metallurgy and surface integrity at the machined surface. Conventional machining, which has been the main machining method, has some limitations related to environmental hazards, cutting fluid costs, and operator health issues that have necessitated the development of sustainable machining. The emphasis in this review has been placed on sustainable grinding techniques such as MQL machining, cryogenic machining, nano-particle MQL machining, high-pressure machining, and solid lubrication machining used to grind titanium alloys and their benefits and limitations. Finally, the review will highlight some of the potential areas for future research and trends on different cooling and lubrication methods in the sustainable grinding of titanium alloys for medical applications. It is believed that this review will be of great benefit to the industries involved in manufacturing titanium-based medical implants.